2020
DOI: 10.21608/epsj.2020.115583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Nigella Sativa Meal on Growth Performance, Some Blood Biochemical and Immune-Responsiveness of Broiler Chicks

Abstract: This experiment was conducted to evaluate the effect of different levels of Nigella sativa meal (NSM) on performance, immunity and some blood biochemical and hematological parameters of broiler chicks. A total of 120, one day-old broiler chicks (Hubbard) were divided into four treatment groups, with three replicates per treatment and 10 chicks per replicate. Chicks in control group were fed basal diet. Birds in treatment groups were fed on diets supplemented with 3, 6 and 9% NSM. Body weights of broilers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…However, broiler chickens fed the diets containing the tested plant protein sources (CM, RSM, BCM, and their combination) displayed significantly less ( P ≤ 0.05) plasma concentrations of MDA than did the control group. The observed increase in plasma concentrations of immunoglobulins (IgG, IgM, and IgA) and TAC in broilers fed the tested plant proteins is in line with those of El-Kashef ( 2020 ). He found that chicks fed diets containing 3 or 6% black cumin seed showed increased levels of blood globulin and leukocyte count in comparison to the control group.…”
Section: Resultssupporting
confidence: 86%
“…However, broiler chickens fed the diets containing the tested plant protein sources (CM, RSM, BCM, and their combination) displayed significantly less ( P ≤ 0.05) plasma concentrations of MDA than did the control group. The observed increase in plasma concentrations of immunoglobulins (IgG, IgM, and IgA) and TAC in broilers fed the tested plant proteins is in line with those of El-Kashef ( 2020 ). He found that chicks fed diets containing 3 or 6% black cumin seed showed increased levels of blood globulin and leukocyte count in comparison to the control group.…”
Section: Resultssupporting
confidence: 86%